2019
DOI: 10.1038/s41401-019-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

Curculigoside facilitates fear extinction and prevents depression-like behaviors in a mouse learned helplessness model through increasing hippocampal BDNF

Abstract: Curculigoside (CUR) is the main active component of traditional Chinese medicine Curculigoorchioides Gaertn (Xianmao in Chinese), which exhibits a variety of pharmacological activities. In this study we investigated the effects of CUR on fear extinction and related depression-like behaviors in mice. In fear conditioning task, we found that administration of CUR (1.6, 8, 40 mg•kg −1 •d −1 , ip, for 7 days) did not affect memory consolidation, but CUR at higher doses (8, 40 mg•kg −1 •d −1) significantly facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 55 publications
4
42
0
Order By: Relevance
“…In can be difficult to observe a clear dosedependent effect when evaluating multiple components or active components from herbal medicine. 25 Surprisingly, the selected dose of donepezil did not promote learning and memory as measured with the MWM. This dose of donepezil may not be sufficient for this specific AD model.…”
Section: Discussionmentioning
confidence: 94%
“…In can be difficult to observe a clear dosedependent effect when evaluating multiple components or active components from herbal medicine. 25 Surprisingly, the selected dose of donepezil did not promote learning and memory as measured with the MWM. This dose of donepezil may not be sufficient for this specific AD model.…”
Section: Discussionmentioning
confidence: 94%
“…PAF and TNF-α levels were detected following the instructions of the assay kits as previously described. 15 The absorbance (OD) was measured at 450 nm wavelength.…”
Section: Elisamentioning
confidence: 99%
“…could prevent depression-like behaviors through increasing BDNF expression. At present, our lab also found that curculigoside prevented depression-like activities through increasing hippocampal BDNF level [96]. Interestingly, most of botanicals and active components facilitate BDNF expression through promoting cAMP/PKA/CREB signaling way.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…At present, most of the studies reported BDNF/TrkB signaling pathway as the therapeutic target for depression by the botanicals, which points out the importance of this specific signaling pathway in the pathogenesis of depression [118]. BDNF/TrkB is a crucial synaptic regulator, which not only correlates with memory but also with mood disorders [96, 119]. Therefore, this target should be kept to screen antidepressants.…”
Section: Future Prospectsmentioning
confidence: 99%